The Sculptural Art of Bernini’s “Apollo and Daphne” from an Iconographic Perspective (Journal of Global Arts Studies, 2025)
Background: The sculpture “Apollo and Daphne” by Gian Lorenzo Bernini, a representative of 17th-century Baroque art, is a classic masterpiece. Existing research has largely focused on Bernini’s artistic career and the creative processes of his works, while the exploration of the deep historical and cultural connotations and the social contextual associations embodied in “Apollo and Daphne” remains insufficient, highlighting the urgent need for interpretation from a multidisciplinary perspective. Purpose: This study aims to analyze the artistic form, symbolic meaning, and cultural context of “Apollo and Daphne” using Panofsky’s iconography, to address gaps in existing research, explore the interaction between the work and social and cultural factors, and open up new avenues for future studies. Methods: This paper uses literature review to outline the creative background of Apollo and Daphne and the research trajectory of iconology, applying Panofsky’s three-stage iconological method along with interdisciplinary perspectives from literature, history, and other fields to deeply interpret the work's profound cultural connotations and symbolic value. Results: Research has found that Bernini’s “Apollo and Daphne” is made of marble, capturing the moment in the myth when Daphne transforms into a laurel tree. The work combines the dynamic aesthetics of the Baroque with the influence of classical sculpture, using exquisite technique to transcend the limitations of the material. It subtly reflects the social and cultural context of its time, and when interpreted from a multidisciplinary perspective, it highlights the multifaceted value of art, history, and culture. Conclusion: This study systematically interprets “Apollo and Daphne” through literature review, iconography, and interdisciplinary methods, verifying the effectiveness of Panofsky’s iconography, presenting the multiple values of the work, and providing interpretive approaches, while also offering a classic case for subsequent research.
Keywords: Bernini; “Apollo and Daphne”; Iconography; Panofsky